2021
DOI: 10.1590/1518-8345.5449.3490
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation and updating of the Risk assessment and management of exposure of health care workers in the context of covid-19 questionnaire

Abstract: Objective: to translate and culturally adapt the Risk assessment and management of exposure of health care workers in the context of covid-19 questionnaire to the Brazilian context and to develop and evaluate a sociodemographic and occupational characterization questionnaire to compose the adapted questionnaire. Method: five stages were conducted to adapt the Risk assessment and management of exposure of health care workers in the context of covid-19 questionnaire, namely: translation, synthesis of the transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Epidemic studies have shown that health professionals are at increased risk for psychological and mental disorders, due to the worsening of working conditions caused by the COVID-19 pandemic [ 15 , 31 , 32 ]. This study presents the high prevalence of depression, anxiety and stress symptoms in health professionals, reinforcing the negative psychological impact of the pandemic on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemic studies have shown that health professionals are at increased risk for psychological and mental disorders, due to the worsening of working conditions caused by the COVID-19 pandemic [ 15 , 31 , 32 ]. This study presents the high prevalence of depression, anxiety and stress symptoms in health professionals, reinforcing the negative psychological impact of the pandemic on mental health.…”
Section: Discussionmentioning
confidence: 99%